Public Policy Transformation in the Face of Digital Disruption in the Health Sector - Ong, Benjamin (Jujurnal Publisher, 2024)
The development of digital technology has brought significant changes in the health sector, creating challenges and opportunities for public policy. Digital disruption in healthcare, such as telemedicine, artificial intelligence (AI), big data, and blockchain, is changing the way governments and healthcare institutions manage the healthcare system. However, the adoption of this technology requires adaptive policy transformation to ensure the effectiveness, accessibility, and safety of health services for the community. This research aims to analyze public policy transformation in the face of digital disruption in the health sector, focusing on regulatory challenges, infrastructure readiness, and ethical aspects and data privacy. The research method used is a literature study (library research) with a qualitative approach, which examines various policies, regulations, and empirical studies related to the implementation of digital technology in the health system. The results of the study show that many countries still face obstacles in adjusting their policies to the development of digitalization, especially related to patient data protection, system interoperability, and gaps in access to health technology. In addition, the integration of AI and big data in healthcare still raises ethical debates, especially in the use of algorithms for medical diagnosis and clinical decision-making. The study highlights the need for more flexible and evidence-based regulation, as well as collaboration between governments, the private sector, and academia in developing policies that are responsive to digital innovation in the health sector. With the right policy transformation, digital disruption can be used to improve the efficiency, accessibility, and quality of healthcare services, while protecting the rights and privacy of patients in the digital era.